2019
DOI: 10.1080/09640568.2018.1540772
|View full text |Cite
|
Sign up to set email alerts
|

Five things government can do to encourage local food contingency plans

Abstract: Severe weather events pose significant risks to food supply chains that are reliant upon critical infrastructures such as road and rail. Can local food procurement arrangements, and contingency plans based on those arrangements, help to ameliorate food shortage in times of crisis? This article explores how governments can empower communities to this end. A broader research project provides the basis of insights and recommendations to aid policy practitioners who seek to develop food-related disaster resilience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Through investigating Swedish textile and clothing firms, the authors identified intangible value propositions, such as organisational culture, leadership, and governance as pivotal design elements for organisational resilience in dynamic market environments. Reis (2019) investigated the food supply network in the Australian regional context of South-East Queensland and focussed on supply disruptions due to extreme weather conditions. Through a literature review and experts' engagement, the author articulated policy recommendations for developing food-related disaster resilience at a community level.…”
Section: Future Researchmentioning
confidence: 99%
“…Through investigating Swedish textile and clothing firms, the authors identified intangible value propositions, such as organisational culture, leadership, and governance as pivotal design elements for organisational resilience in dynamic market environments. Reis (2019) investigated the food supply network in the Australian regional context of South-East Queensland and focussed on supply disruptions due to extreme weather conditions. Through a literature review and experts' engagement, the author articulated policy recommendations for developing food-related disaster resilience at a community level.…”
Section: Future Researchmentioning
confidence: 99%
“…Regan et al (2015) derive a conceptual framework from the 2013 aftermath of the horsemeat adulteration incident in the UK and Ireland. As for natural disaster, Smith et al (2015) examine the resilience of long vs short FSC; Reis (2019) explores the role of government in coping with the 2011 Queensland flood crisis in Australia. To our knowledge, before the COVID-19 outbreak, there was only one discourse on the impacts of the influenza pandemic on the FSC (Ekici et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This will enable them to build their reputation and avoid negative criticism from society, as well as making them more able to respond to policy and regulatory risks [66], [115]. Reis [116] summarized the key issues for governments formulating food contingency plans, which include building a shared control and responsibility network among AFSC stakeholders, and involving more stakeholders in decision making. These measures may mitigate the effects of severe weather events.…”
Section: A Thematic Analysismentioning
confidence: 99%